COMPOSITION IN LA LA LAND - Agnia, Felia Arlitha; Sari, Maya Purnama (Seni Media Rekam ISI Surakarta, 2021)
The film La La Land is a musical drama that is exceptionally well-made and features some of the best cinematography. As a result, this picture garnered numerous awards and earned a substantial income. This study seeks to analyze the visual composition in the film La La Land. This research uses qualitative descriptive approach with the film La La Land as the object. The data analysis process incorporated interpretative visual techniques, most notably interpretive video analysis. The results demonstrate that La La Land employs both symmetrical and asymmetrical (Rules of Thirds) compositions to create an aesthetic image. This composition adds excitement and vitality to the film La La Land.